2019
DOI: 10.15285/maruaebd.586835
|View full text |Cite
|
Sign up to set email alerts
|

Kademeler arası geçiş ve sınav sisteminde yapılan değişikliklere ilişkin okul yöneticilerinin görüşleri

Abstract: ÖzBu araştırmanın amacı, Türkiye' de kademeler arası geçiş ve sınav sisteminde yapılan değişikliklere ilişkin okul yöneticilerinin görüşlerinin incelenmesidir. Nitel araştırma yöntemlerinden fenomenoloji deseniyle yürütülmüş olan bu çalışmanın verileri, yüz yüze görüşme yoluyla yarı yapılandırılmış bir görüşme formu kullanılarak elde edilmiştir. Araştırma kapsamında İstanbul ili Çekmeköy ve Sancaktepe ilçelerinde bulunan farklı okul türlerinde görev yapan 22 okul yöneticisi ile görüşülmüştür. Görüşmeler sonucu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
1
3
0
1
Order By: Relevance
“…All of the interviewed administrators stated that the constant change in the system reduces the motivation of the students and their parents are very uncomfortable with these changes. Demirbilek & Levent (2019) revealed similar results to our study and found that the changes made in the examination system undesirably affects the motivation of the students. Akbaba (2006) underlined that motivation directly affects student achievement.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…All of the interviewed administrators stated that the constant change in the system reduces the motivation of the students and their parents are very uncomfortable with these changes. Demirbilek & Levent (2019) revealed similar results to our study and found that the changes made in the examination system undesirably affects the motivation of the students. Akbaba (2006) underlined that motivation directly affects student achievement.…”
Section: Resultssupporting
confidence: 90%
“…Only one of the interviewed administrators expressed a positive opinion about the system. Demirbilek & Levent (2019) pointed out in their research that school administrators have a negative view of the system due to some downsides.…”
Section: Resultsmentioning
confidence: 99%
“…The findings show that major changes in the transition system, regardless of its structure and regulations, lead to a significant and negative change in student achievement. As shown in studies before, the regulations in the transition systems negatively affect the students, parents and administrators (Demirbilek & Levent, 2019;Dinç et al, 2014;Zayimoğlu Öztürk, 2014). For the first time, the present study showed that major changes in the system negatively affect student achievement.…”
Section: Discussionmentioning
confidence: 93%
“…The major aim of these changes is to take a step towards the improvement of the education system. However, related research shows that students, parents and administrators complain and are negatively affected by the comprehensive changes made in both the university entrance system and the transition system to secondary education, (Demirbilek & Levent, 2019;Dinç et al, 2014;Zayimoğlu Öztürk, 2014). Since the past, it has been seen that in the discussions and practices regarding the education system in Turkey, a great deal of value has been attributed to the changes in examination systems (Gür & Çelik, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ancak LGS hakkında okul yöneticileri ile yapılan çalışma mevcut değildir. Literatürde okul yöneticileri ile yapılan çalışmalar genel ortaöğretim geçiş sistemlerine ve LGS'den önce uygulanan sistemlere yönelik sürdürülmüştür (Demirbilek & Levent, 2019). Bundan dolayı sistemin bir diğer paydaşı olan okul yönetici görüşlerinin alınmasının alan literatürüne katkı sağlayacağı düşünülmektedir.…”
Section: Introductionunclassified